2011
DOI: 10.15835/nsb325877
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Virulence Gene Activity of Agrobacterium in Muskmelon (Cucumis melo L.) cv. ‘Birdie’

Abstract: Muskmelon (Cucumis melo L.) cultivar 'Birdie' , was evaluated for its response to the tumorigenic Agrobacterium tumefaciens and the oncogenic A. rhizogenes strains. Stem and petiole of three week-old in vitro-grown muskmelon plants were inoculated with five strains of A. tumefaciens and A. rhizogenes each and observed phenotypic expressions i.e. induction of crown galls and hairy roots. This phenotypic expression was efficaciously increased when virulence gene activity of different strains of two Agrobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Acetosyringone, a monocyclic phenolic compound, plays an important role on vir gene activation and T-DNA transfer (Ridgway et al 2004). Mohiuddin et al (2011) reported that acetosyringone, an amino acid derivative, is essential for biological activity and maintenance of vir gene expression in host cells. Recently, Srinivasan et al (2014) reported that carrot transformation efficiency of MTCC 2364 and MTCC 532 was highly dependent on the acetosyringone concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Acetosyringone, a monocyclic phenolic compound, plays an important role on vir gene activation and T-DNA transfer (Ridgway et al 2004). Mohiuddin et al (2011) reported that acetosyringone, an amino acid derivative, is essential for biological activity and maintenance of vir gene expression in host cells. Recently, Srinivasan et al (2014) reported that carrot transformation efficiency of MTCC 2364 and MTCC 532 was highly dependent on the acetosyringone concentration.…”
Section: Discussionmentioning
confidence: 99%
“…13,19 The effect that Agrobacterium strain and the type of explant had on the transformation efficiency of cucurbits was well documented. [20][21][22] To achieve an optimized condition for the establishment, virulence of four Agrobacterium strains (MSU440, A4, A13, ACTT 15834) were compared against three types of colocynth explants (leaf, excised shoot and hypocotyl). According to the results (Figure 1), all the studied strains were virulent against the leaf and excised shoot explants.…”
Section: Resultsmentioning
confidence: 99%
“…28 This compound also increased the virulence of the strains ACTT 15834 and 8196 on Muskmelon (Cucumis melo). 22…”
Section: Co-cultivation Periodmentioning
confidence: 99%
“…AS is an amino acid derivative and a phenolic compound, which must be constant for biological activity and maintenance of vir gene expression in Muskmelon explants. 23 Many other reports also pointed out that the vir genes are inducible in response to the monocyclic phenolic compound like AS. 24 The results obtained from higher (20 mg l-1) concentration of AS indicated an inhibitory action rather than stimulatory.…”
Section: Discussionmentioning
confidence: 99%